The Effect of a Constant Electrical Field on Osseointegration after Immediate Implantation in Dog Mandibles: A Preliminary Study - Yadollah Soleymani Shayesteh, DDS, MS;1 Behnam Eslami, DDS, MS;2 (Journal of Prosthodontics, 2007)
The long time span between insertion of implants and functional rehabilitation often inconveniences patients. Accelerating bone growth around dental implants can shorten this time span